Iodine Deficiency Disorders In Pregnant Women and Neonates - A. Agnihotri, Dr. Madhuri; Ratnani, Dr. Rekha (International Journal of Innovative Research in Medical Science, 2017)
Aim - Iodine Deficiency Disorders in Pregnant Women and Neonates at CCMMC Hospital Durg. Material and Methods - Investigation was carried out in 23 pregnant women suffering from congenital hypothyroidism and compared with 30 normal control group composed of healthy pregnant women and followed-up to one month of delivery of the neonates. Cord blood samples was collected after birth of new born in specimen tube, and 5 ml blood will be collected in a dry, clean, plane tube from maternal and fetal. After clotting of blood, it is centrifuged at 3000 rpm. for 10 minutes. Serum will separated for the analysis of thyroid profile such as TSH, T4, T3, using ELISA and reagents kits will purchased from accu-bind. A spot morning urine sample from each mother was collected and assayed in duplicates for the determination of urinary iodide concentration (UIC) using ammonium persulphate digestion method Results - Significance of study- The emphasis on Iodine supplementation during pregnancy is not a routine practice in Durg district. In such situation an adequate dietary intake of Iodine throughout the gestation period has to be investigated. Therefore the present study has been planned to assess the maternal iodine status and thyroid function at the first second & third trimester and its influence on neonatal thyroid function and lastly screening of congenital hypothyroidism in neonates of Chhattisgarh, with a view to strongly recommend the implementation of neonatal screening programmer for iodine so that the optimal mental development of children can be achieved.